Informality and long-run growth - Frédéric Docquier; Tobias Müller; Joaquín Naval (Fondation pour les études et recherches sur le développement international (FERDI), 2014)
One of the most salient features of developing economies is the existence of a large informal sector. This paper uses quantitative theory to study the dynamic implications of informality on wage inequality, human capital accumulation, child labor and long-run growth. Our model can generate transitory informality equilibria or informality-induced poverty traps. Its calibration reveals that the case for the poverty-trap hypothesis is strong: although informality serves to protect low-skilled workers from extreme poverty in the short-run, it prevents income convergence between developed and developing nations in the long run. Sudden elimination of informality would induce severe welfare losses for several generations on the transition path. Hence, we examine the effectiveness of different development policies to exit the poverty trap. Our numerical experiments show that using means-tested education subsidies is the most costeffective single policy option. However, for longer time horizons, or as the economy gets closer to the poverty trap threshold, combining means-tested education and wage subsidies is even more effective.
Keywords: O11; O15; O17; 330